1994
DOI: 10.1007/bf02087432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a model of canine jejunoileal orthotopic autotransplantation on jejunal and ileal transport of water and electrolytes

Abstract: Canine jejunoileal transplantation induces an early profuse watery diarrhea of uncertain etiology. Our aim was to determine the temporal effects of a canine model of jejunoileal autotransplantation (a model devoid of confounding effects of ischemia-reperfusion or immune rejection) on basal jejunal and ileal absorption of water and electrolytes to determine if impaired absorption is responsible for the diarrhea. Our hypothesis was that net absorption of water and electrolytes in an enterically isolated loop wou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…55 Experimental evidence also indicates that the chronic extrinsic denervation of the small intestine does not affect net intestinal absorption of water and electrolytes. [55][56][57][58][59][60][61][62][63][64][65][66][67] We have also shown that CGx does not affect Na ϩ intake in rats fed 2% NaCl. 68 The exact hemodynamic mechanism by which CGx affects Ang II salt hypertension is still not completely clear and needs to be investigated further by chronic instrumentation of rats for measurements of cardiac output and total peripheral resistance determination.…”
Section: Discussionmentioning
confidence: 99%
“…55 Experimental evidence also indicates that the chronic extrinsic denervation of the small intestine does not affect net intestinal absorption of water and electrolytes. [55][56][57][58][59][60][61][62][63][64][65][66][67] We have also shown that CGx does not affect Na ϩ intake in rats fed 2% NaCl. 68 The exact hemodynamic mechanism by which CGx affects Ang II salt hypertension is still not completely clear and needs to be investigated further by chronic instrumentation of rats for measurements of cardiac output and total peripheral resistance determination.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is associated with rejection and frequently mandates augmented immunosuppression. However, some cases remain of unclear etiology, and detailed basic investigation in the past implicated altered motility patterns, denervation with altered sympathetic tone, or other factors (33,34). Recent clinical investigation suggests that novel and specific pathogens not described after other solid-organ transplants may infect the transplanted intestinal allograft.…”
Section: Medical Progressmentioning
confidence: 99%
“…Net absorption has also been evaluated in large-animal models in vivo. Sarr and colleagues [23,[31][32][33][34] explored this topic in-depth in a canine model of jejunoileal auto transplantation devoid of immune effects or ischemia/ reperfusion injury [9], Although no significant differences were noted in net absorption of water and electrolytes in entericallv isolated intestinal loops (as compared with controls), when studied in the in situ jejunum [33] and in the in situ ileum [34], net absorption was decreased 2 weeks after surgery, but returned toward normal by 8 weeks postoperatively, coinciding with the time the diar rhea resolved. Similar results were noted by Dennison et al [35] and Collin et al [36] in the ileum.…”
Section: Absorption O F Water and Electrolytesmentioning
confidence: 99%